Performance Of Bari Mango (Mangifera indica L.) Varieties In Chittagong Region (Bangladesh Journal of Agricultural Research, 2013)
Five mango varieties developed by Bangladesh Agricultural Research Institute (BARI) were evaluated at ARS, Pahartali, Chittagong during January to June 2012 to find out the suitable variety. The earliest flowering as well as harvesting were observed in BARI Aam-1 and the latest in BARI Aam-8. Number of fruits per tree varied from 51 to 117. Maximum number of fruits (117) per tree was obtained from BARI Aam-8, while minimum fruits (51) from BARI Aam-4 (Hybrid). The heaviest fruit (373.0 g) was obtained from BARI Aam-4 (Hybrid), while the lightest fruit (172.6 g) was in BARI Aam-3. Maximum yield per plant was found in BARI Aam-8 (33.59 kg) followed by BARI Aam-4 (19.02 kg), whereas it was lowest in BARI Aam-1(14.42 kg). The highest edible portion (78.66 %) was recorded in BARI Aam-4, while the lowest (65.99%) was obtained from BARI Aam-1. The highest TSS content (21.36%) was recorded in BARI Aam-3, whereas the lowest TSS content (16.51%) was observed in BARI Aam-2. Bangladesh J. Agril. Res. 38(2): 203-209, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15883